Sofosbuvir plus ribavirin for hepatitis C virus-associated cryoglobulinaemia vasculitis: VASCUVALDIC study. Issue 10 (13th November 2015) - Saadoun, David; Thibault, Vincent; Si Ahmed, Si Nafa; Alric, Laurent; Mallet, Maxime; Guillaud, Constance; Izzedine, Hassane; Plaisier, Aurélie; Fontaine, Hélène; Costopoulos, Myrto; Le Garff-Tavernier, Magali; Hezode, Christophe; et al.
Abstract : Background: Hepatitis C virus (HCV) is the aetiological agent for most cases of cryoglobulinaemia vasculitis. Interferon-containing regimens are associated with important side effects and may exacerbate the vasculitis. Objective: To evaluate safety and efficacy of an oral interferon-free regimen, sofosbuvir plus ribavirin, in HCV-cryoglobulinaemia vasculitis. Patients and methods: We enrolled 24 consecutive patients (median age of 56.5 years and 46% of women) with HCV-cryoglobulinaemia vasculitis. Sofosbuvir (400 mg/day) was associated with ribavirin (200–1400 mg/day), for 24 weeks. The primary efficacy end point was a complete clinical response of the vasculitis at the end of treatment (week 24). Results: Main features of HCV-cryoglobulinaemia vasculitis included purpura and peripheral neuropathy (67%), arthralgia (58%), glomerulonephritis (21%) and skin ulcers (12%). Twenty-one patients (87.5%) were complete clinical response at week 24. Complete clinical response was achieved in six (25%) patients at week 4, four (16.6%) at week 8, seven (29.2%) at week 12, three (12.5%) at week 16 and one (4.2%) at week 20. The cryoglobulin level decreased from 0.35 (0.16–0.83) at baseline to 0.15 (0.05–0.45) g/L at week 24. The C4 serum level increased from 0.10 (0.07–0.19) to 0.17 (0.09–0.23) g/L at week 24. Seventy-four per cent of patients had a sustained virological response at week 12 post treatment. The most common side effects were fatigue, insomnia and anaemia. Two serious adverse events were observed. Conclusions: Sofosbuvir plus ribavirin combination was associated with a high rate of complete clinical response and a low rate of serious adverse events in HCV-cryoglobulinaemia vasculitis.